Winter soldier (2012), volume 1 ebook - Brubaker, Ed (Winter Soldier (2012), 2013)
Collects Winter Soldier #1-5 & Fear Itself #7.1: Captain America. He's been Bucky and Captain America - now, James Barnes returns to the role of the Winter Soldier! When ex-Russian sleeper agents awaken, Bucky and the Black Widow must go on the hunt for men trained by the Winter Soldier himself. But when the trail leads to Latveria, Bucky comes face-to-face with Dr. Doom!